The peptidases of Trypanosoma cruzi: digestive enzymes, virulence factors, and mediators of autophagy and programmed cell death - Alvarez, Vanina Eder (2012)
Trypanosoma cruzi, the agent of the American Trypanosomiasis, Chagas disease, contains cysteine, serine, threonine, aspartyl and metallo peptidases. The most abundant among these enzymes is cruzipain, a cysteine proteinase expressed as a mixture of isoforms, some of them membrane-bound. The enzyme is an immunodominant antigen in human chronic Chagas disease and seems to be important in the host/parasite relationship. Inhibitors of cruzipain kill the parasite and cure infected mice, thus validating the enzyme as a very promising target for the development of new drugs against the disease. In addition, a 30 kDa cathepsin B-like enzyme, two metacaspases and two autophagins have been described. Serine peptidases described in the parasite include oligopeptidase B, a member of the prolyl oligopeptidase family involved in Ca 2+- signaling during mammalian cell invasion; a prolyl endopeptidase (Tc80), against which inhibitors are being developed, and a lysosomal serine carboxypeptidase. Metallopeptidases homologous to the gp63 of Leishmania spp. are present, as well as two metallocarboxypeptidases belonging to the M32 family, previously found only in prokaryotes. The proteasome has properties similar to those of other eukaryotes, and its inhibition by lactacystin blocks some differentiation steps in the life cycle of the parasite. This article is part of a Special Issue entitled: Proteolysis 50 years after the discovery of lysosome. © 2011 Elsevier B.V. All rights reserved.